THE COMPETENCE OF THE LEADER AND ITS IMPACT ON THE STRATEGIC PLANNING OF EDUCATIONAL INSTITUTIONS - Rabab Ameen F; Zahraa Abdulrazzaq G; Mejbel Isheer Meteab AL Matrood (Scholar Express Journals, 2022)
Leadership is the positive activity that a specific person undertakes in the field of administrative supervision on others to achieve a specific goal by means of influencing and appealing, and by using official authority to the appropriate extent and when necessary, and among the new skills required for an effective administrative leader is proficiency in dealing with computers and techniques Information and communication, and the latter represented in technical skill, while strategic planning is an administrative process that includes all parts of the organization and involves taking decisions to determine the future of the organization based on the availability of comprehensive information about the institution and its environment to determine the desired production requirements
Keywords: Leader; Strategic Planning; Educational Institutions